The Tradition of Serbia’s Liberation Wars (1912–1918) in Serbian Church Architecture Between the Two World Wars - Stefanović, Tadija B. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Between 1918 and 1941, Serbian church architecture reflected an atmosphere of renewal in national terms as much as in the spiritual life. In order to preserve the memory of the Serbian soldier—the national hero and martyr—a concept for a memorial church was conceived, dedicated to the Liberation Wars of 1912–1918. This allowed the Serbs to discover new dimensions of their national identity, which was deeply rooted in the soldier cult. In the atmosphere of the extensive social renewal and founded on the Orthodox identity, a symbolic bond between the Liberation Wars of 1912–1918 and the Kosovo spiritual heritage was sought. It highlighted the Serbian soldier, from the martyr Prince Lazar Hrebeljanović in 1389 to the soldiers of Crown Prince Alexander I Karađorđević who fell between 1912 and 1918. Thus, their national roles were ritualized in both symbolic and physical terms, bridging the distances they occupied within the coherent system of practical needs. This signified that the soldiers who fell during the Liberation Wars of 1912–1918 were heroes and martyrs with a national mission. During the formation of interwar Yugoslavia, this had a positive impact on the national preservation of the Serbian people, especially under the constant pressure of Yugoslav generalization. The memory of the Serbian soldier was also used to commemorate the military national tradition in a new type of church—a memorial church, which represented a symbiosis of religious and funerary elements. These churches were built in cities and villages, near former battlefields, and wherever the need was felt. Serbian heroes were symbolically and physically enshrined in the ossuaries of these churches. They were deeply saturated with Orthodox religious identity, medieval heritage, and the sentiment of the recent war history. Thus, a framework of interpretation was constructed, memorializing the heroism and martyrdom of the Serbian soldier from the Liberation Wars of 1912–1918 within the memorial church, which provided the Serbian nation with a range of opportunities for affirmation, identification, and national recognition.